IMPULSIVITY IS AN INDIVIDUAL BEHAVIORAL CHARACTERISTIC OF THE SAFETY CULTURE AND HEALTHY LIFESTYLE OF STUDENTS (Education in the 21st Century, 2023)
The study results of the impulsivity levels of students of the humanities when studying the discipline "Human Life Safety" are presented. It is found that among students of the specialties "Modern Foreign Languages: majoring in Teaching", "Cultural Studies", "Communicative Design" and "Design of the Subject-spatial Environment", an average moderate level of impulsiveness prevails, which is expressed in their ability to make decisions more thoughtfully in the case of a choice of actions and possible consequences. They are emotionally restrained, able to control their behavior and plan their actions and deeds. The identification of the level of students’ impulsiveness in the educational process is a key condition for the formation of safety culture and healthy lifestyle. In the case of detecting of high indicators of the level of impulsivity, it is vital to draw up an individual self-education program aimed at reducing emotional stress, increasing self-control and goal orientation.
Keywords: Life safety culture; healthy lifestyle; impulsivity; students